Peruvian health services users’ satisfaction: Socio-demographic factors and accessibility. Peru 2000 - Seclén-Palacin, Juan (2005)
Objectives: To determine users’ satisfaction in Peru Ministry of Health’s health centers (HC) and hospitals, to analyze the relation between users’ satisfaction and the socioeconomic variable, and to identify both the sociodemographic and accessibility factors related. Materials and Methods: Secondary analysis of the database of Peruvian Living Standards Survey (PLSS), year 2000; 376 health center and 327 hospital users were studied. The study variables were users’ satisfaction, socioeconomic level, socio-demographic variables and accessibility to care. Descriptive and multivariate statistics were applied. Results: The health center users show patterns different to the hospital users. Satisfaction was respectively 68,1% and 62,1% for health centers and hospitals. The users with less socioeconomic level showed greater satisfaction. Age, education, distance to health facilities and waiting time were related with users’ satisfaction. Conclusions: Socio-demographic, economic and accessibility to care factors associated to users’ satisfaction show specific characteristics according to location, probably due to difference between health facilities populations.